Current practices in school athletics in fourteen public secondary schools in Manila - Sevilla, Aurora Villacorta 1928- (s.n.], 1961)
The prevailing practices in school athletics in 14 public secondary schools in Manila are determined in this study in order to minimize, if not totally eliminate, harmful athletic practices that are detrimental to the participants. It is also determined in this study the prevailing practices which contribute to the acquisition of educational values for the youth. Lastly, the study offers solutions or suggestions to correct or minimize existing undesirable practices which threaten to undermine the good in athletics.